PEREMPUAN DALAM PENDIDIKAN ISLAM MENURUT PEMIKIRAN SITI WALIDAH - Aminah, Siti; Hifza, Hifza; Purnamasari, Wulan (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
This research departs from the gaps that occur in society, especially the classification between men and women, especially in equal rights and obligations, where there is still discrimination against women in the realisation of equal rights and obligations even though the competency factor is not considered in this case, but only the social strata factor. Not only that, this discrimination among the community is basically not only detrimental to women, but the nation, especially the Indonesian nation because the potential possessed by women is sometimes ignored and not appreciated. This is due to the lack of awareness of tolerance and mutual respect, especially in the pre-independence era. The focus of this research is the position of women in Islamic education, the role of women as educators according to Siti Walidah's thoughts and the correlation between religious views, state ideology and Siti Walidah's thoughts on the role of women in Islamic education with the reality that occurs in Indonesia. This research uses the concept of library research. Data collection techniques with character studies and related sources. The results of the study can be concluded: the position and role of women in education is equal to men, in reality there is a gap that occurs in society about equal rights and obligations between men and women